NILAI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DALAM KURIKULUM MADRASAH - Rofik Rofik (Jurnal Pendidikan Agama Islam, 2015)
One criticism to Learning of Islamic Culture History (SKI) in Madrasah / School is memorization (rote) stigma. This criticism is quite reasonable, because in practical terms Islam Cultural History as a subject is often taught in informative or just in rote. One fact is reflected in the allotment of instructional time in the curriculum of 1994, for example, only one lesson hour. Medium scope and sequence of material is very wide and deep. This article aims to eliminate the stigma by finding Learning Value of Cultural History of Islam in the grand design SKI Content Standards in the madrasa curriculum of 1994, 2004, 2006, 2008 (specially PAI and Arabic Madrasa) and 2013. In order to be found on the basis of their human values, namely Islam, as a religion, then traced to the values of Islam to the Islamic Cultural History Value and finally to the Value of Learning History Islamic Cultural embodied in four categories, namely material value, formal value, functional value, and essential values.